Removal of methylene blue dye from textile industry wastewater using green synthesized Teff straw assisted ZnO nanoparticle - Getachew L. Rorissa; Ermias A. Tesema; Reddy Prasad D.M.; Abdisa R. Hunde; Sirno Y. Beyena; Meron A. Biru; Dereje T. Mekonnen; Tebelay L. Adnualem (Scientific Reports)
Abstract Methylene blue dye contamination poses serious environmental and health risks, necessitating efficient removal methods. Conventional Zinc Oxide (ZnO) nanoparticles synthesized chemically face issues like toxicity, instability, and agglomeration, reducing their effectiveness. This study explores the green synthesis, characterization, and application of teff straw-assisted ZnO nanoparticles, using neem leaf extract as a capping agent, for MBD removal from textile wastewater. Characterization via X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) confirmed functionalization, with an average crystalline size of 27.196 nm. Adsorption experiments analyzed the impact of pH, adsorbent dose, contact time, and initial dye concentration, while Response Surface Methodology (RSM) with a Central Composite Design (CCD) optimized conditions, achieving 99.77% removal efficiency at pH 6.9, 68.5 mg/L dye concentration, 0.265 g adsorbent dose, and 77.87 min contact time, fitting the Freundlich isotherm model (R² = 0.99). Real textile wastewater treatment showed 92.5% removal efficiency, proving teff straw-assisted ZnO nanoparticles as a sustainable, eco-friendly alternative for wastewater treatment.